2022
DOI: 10.3390/ijerph191912750
|View full text |Cite
|
Sign up to set email alerts
|

University Students Eating Habits: Normal Semester vs. Lockdown Period Caused by COVID-19 Pandemic

Abstract: In the face of the COVID-19 pandemic, university students’ eating habits may change due to the stress caused by mandatory full lockdown and social isolation, as well as uncertainty about their academic future. An analysis of 332 Portuguese university students from different areas of study was carried out through an online questionnaire to verify if the lockdown period caused by COVID-19 had any influence on the students’ eating habits, as well as if this differed among students from health sciences courses and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 13 publications
2
5
0
2
Order By: Relevance
“…A study carried out on Portuguese university students showed that healthier eating habits were adopted by the students during the lockdown period compared to a typical semester period. Such healthier behaviors included reduced meal delivery, a lower intake of sugar, salt, and fast food, as well as higher engagement in physical activities and more consumption of fruits, vegetables, and legumes [35]. The decreased physical activity levels observed in our study, especially among females, are consistent with global trends during the pandemic [27,[32][33][34].…”
Section: Changes In Lifestyle Behaviors and Eating Habitssupporting
confidence: 82%
“…A study carried out on Portuguese university students showed that healthier eating habits were adopted by the students during the lockdown period compared to a typical semester period. Such healthier behaviors included reduced meal delivery, a lower intake of sugar, salt, and fast food, as well as higher engagement in physical activities and more consumption of fruits, vegetables, and legumes [35]. The decreased physical activity levels observed in our study, especially among females, are consistent with global trends during the pandemic [27,[32][33][34].…”
Section: Changes In Lifestyle Behaviors and Eating Habitssupporting
confidence: 82%
“…Another Portuguese study, however, found that 58.2% of the participants increased the consumption of fruits and vegetables but reduced the consumption of pre-cooked meals and sugar-sweetened beverages (36). Similar studies carried out in other countries highlighted the improvement in nutritional habits including increased intake of fruits, vegetables, yogurt, legumes, and eggs during the lockdown (13,15,24,25,34,(37)(38)(39)(40)(41).…”
Section: Discussionsupporting
confidence: 55%
“…Monteiro et al showed that healthier eating habits were adopted by university students during the lockdown period compared to a typical semester period. Their selfreported healthier eating habits included limited application of meal delivery platforms, less consumption of fast food, pre-cooked meals, foods high in sugar and salt, and sugar-sweetened beverages, more consumption of fruits, vegetables, and legumes, as well as more serious engagement in physical activities (34). Enriquez-Martinez et al also conducted a study on 6,325 participants aged over 18 years from five countries, and demonstrated that more favorable patterns of eating choice were observed among those who changed their eating habits compared to those who did not change their eating habits (35).…”
Section: Discussionmentioning
confidence: 99%
“…GALANIS et al, 2021;HAUG et al, 2020;IEZADI et al, 2021). Além disso, estudos realizados destacaram como, consequências para os alunos que permaneceram em ensino remoto durante o período pandêmico, alterações em hábitos alimentares, alterações cardiovasculares, distúrbios do sono, sedentarismo, distúrbios psicológicos, depressão, ansiedade e outros(BIELEC; KWAŚNA, 2022;BIRMINGHAM et al, 2023;BRANQUINHO et al, 2022;JAHRAMI et al, 2022;MONTEIRO;FERREIRA-PÊGO, 2022).…”
Section: Resultsunclassified